Pengaruh Kualitas dan Inovasi Pelayanan Terhadap Kepercayaan Masyarakat Melalui Kepuasan Masyarakat Sebagai Variabel Intervening Pada Dinas Kependudukan dan Pencatatan Sipil Kabupaten Banyuwangi - Mochamad Muzaki; Ni Nyoman Putu Martini; Arik Susbiyani; Nurul Qomariah (STIE Mandala Jember, 2023)
Public trust is important in order to achieve clean government and good governance. These goals are achieved through providing high-quality services that are enjoyed by the public and through innovation that leads to community satisfaction. We will to investigated the service quality and new service innovation affect public trust, with satisfaction as a possible intervention variable. We will to observe the people who work in the Department of Population and Civil Registration in Banyuwangi Regency during March-June 2022. This study is a quantitative study focusing on civil registration in Banyuwangi. This study includes 1.351.168 people living in Banyuwangi, Indonesia, and a sample was chosen using a purposive sampling technique to include as many respondents as possible who have used population service innovations. A questionnaire will used to make a primary data, with respondents rating their agreement on a Likert scale. Path analysis is a data analysis technique that can be used to explore relationships between different variables. The results show that service quality make a positive and significant impact on community satisfaction, service innovation make a positive and significant impact on community satisfaction, community satisfaction make a positive and significant impact on trust, and repair quality contains a positive and significant impact on trust Significant impact, service innovation incorporates a positive and signnificant impact on trust, service quality features a positive and significant indirect impact on trust through community satisfaction Service innovation includes a positive and significant indirect impact on charitable trust through community satisfaction with service Significant indirect effects.